Determinants and consequences of clawback provisions in management compensation contracts: a structured literature review on empirical evidence - Patrick Velte (Business Research, 2020)
The goal of this systematic literature review is to provide a detailed understanding of the determinants and consequences of clawback provisions in management compensation contracts, motivated by the increasing global regulatory, practical, and academic importance of implementing this new corporate governance tool. We identify 44 empirical (archival and experimental) studies on this topic and review them based on an agency-theoretical framework. Our review of empirical clawback research offers insights into this growing field and supports future researchers in developing new research questions. Our main results are as follows. First, we still know very little about the drivers of clawback adoption, as prior research concentrated on the consequences of clawback provisions. Second, many studies indicate that clawbacks lead to better earnings quality (reduced re-/misstatements), better pay-for-performance sensitivity, increased firm performance, greater value relevance, and lower overinvestment. While there are indications that clawbacks may serve an incentive-alignment function for managers, their contribution may be dependent on other corporate governance mechanisms, e.g. board composition, as significant moderators. We develop a research agenda with detailed recommendations for future research from methodological and content perspectives. We expect that the research activity in this field regarding the European capital market will increase in light of the EU shareholder rights Directive of 2017.
Keywords: M41; M48; Q3; Q56; 650; Board composition; Management compensation; Financialrestatements; Earnings management; Clawbacks; Principal agenttheory